Research through design: qualitative analysis to evaluate the usability - Costa, António Pedro
The present need to identify and understand non-measurable/ non-quantifiable of the user experience with software has been the moto for may researchers in the area of Human Computer Interaction (HCI) to adopt qualitative methods. On the other hand, the use of qualitative analysis to support software has been growing. The integration of these types of tools in research is accompanied by an increase in the number of software packages available. Depending on the design and research questions, researchers can explore various solutions available in the market. Thus, it is urgent to ensure that these tools, apart from containing the necessary functionality for the purposes of research projects, are also usable. This study presents an assessment of the usability of the qualitative data analysis software webQDA® (version 2.0). To assess its usability, Content Analysis was used. The results indicate that the current version is “acceptable” in terms of usability, as users, in general, show a positive perception is perceived from users with completed PhDs as compared to those who are still doing their PhDs; no relevant differences can be found between the views obtained from different professional or research areas, although a more positive assessment may be drawn from Education and Teaching. Suggestions for future studies are put forward, even though we recognise that, in spite of most studies on usability defining quantitative metrics, the present study is offered as a contribution that aims to show that qualitative analysis has a great potential to deepen various dimensions of usability and functional and emotional interrelationships that are not by any means quantifiable.